Combinatorial Enzyme Design Probes Allostery and Cooperativity in the Trypsin Fold - Page, Michael J. (2010)
Converting one enzyme into another is challenging due to the uneven distribution of important amino acids for function in both protein sequence and structure. We report a strategy for protein engineering allowing an organized mixing and matching of genetic material that leverages lower throughput with increased quality of screens. Our approach successfully tested the contribution of each surface exposed loop in the trypsin fold alone and the cooperativity of their combinations towards building the substrate selectivity and Na(+)-dependent allosteric activation of the protease domain of human coagulation factor Xa into a bacterial trypsin. As the created proteases lack additional protein domains and protein co-factor activation mechanism requisite for the complexity of blood coagulation, they are stepping-stones towards further understanding and engineering of artificial clotting factors.